Benchmarking as an ideal method for optimising rehabilitation. (12th November 2014) - Fuhrlaender, Bernd
Abstract : Objective : To show that benchmarking, through internal and/or external structured comparisons, is the ideal method to conduct more efficient and more effective processes. The presentation illustrates that benchmarking, especially in the rehabilitation of accident victims, is the appropriate method to use to focus on the various interests, backgrounds and individual needs of accident victims during therapy management. The objective of the project, Benchmarking the Effectiveness and Efficiency of Case Management, was to identify usable examples and methods for optimizing therapy management based on structured comparisons. The project, in which fourteen insurance carriers took part, was initiated by the German association of accident insurance carriers, Deutsche Gesetzliche Unfallversicherung (DGUV). The Benchmarking focused on how the insurance carriers handled the rehabilitation process, from the time of the accident to the end of the treatment period or the occupational reintegration. The entire rehabilitation process, including the case work as well as the active planning, cooperation and monitoring of the medical, professional and social rehabilitation was divided into several segments. In this way, regardless of differences in the various procedures of the participants, fair and speedy comparisons of the segments could be established. For example: Analysis of all the processes and structures of therapy management Parameters for accident severity and frequency Resources used (overhead, personnel cost, time) Assessment of existing management tools Results : None of the participating carriers had the "ideal organization" of his therapy management program. Nevertheless, clear "Best Practice" examples were identified within the respective sub processes. From this, several recommendations were made. The presentation points out the most significant ones. Conclusion : The Benchmarking project was successful. The participating carriers followed the recommendations and thereby increased the efficiency and effectiveness of their therapy management program.